PELATIHAN PEMANFAATAN PLATFORM PADLET SEBAGAI MEDIA PEMBELAJARAN DIGITAL UNTUK GURU SD - Nurlaily, Vivi Astuti; Dayu, Dian Permatasari Kusuma; Wiryanto, Wiryanto; Suprayitno, Suprayitno (Abdi Masya, 2025)
The development of the world of technology in the current era can be a strong impetus to optimize technology in various fields, including the world of education, one of which is in the form of digital learning media. Elementary school teachers in Trenggalek Regency find it difficult to use digital learning media due to lack of knowledge and training regarding the use of digital media, teachers still do not master the use of digital platforms that can be used as learning media, variations in the learning process really need to be optimized to make students enthusiastic and not bored during learning, teachers need training related to the use of digital learning media. Padlet is a digital learning media that is easy for educators and students to use to carry out distance learning. Participants in the training activity were 302 elementary school teachers in Munjungan District, Trenggalek Regency. This training activity was carried out in a hybrid manner; offline activities were located at SMP N 1 Munjungan in Trenggalek Regency, and carried out simultaneously with online activities carried out via Zoom meeting. The training activities were carried out in several stages, namely preparation, implementation, and mentoring. The training activities were carried out in two sessions: presentation of material, questions and answers, and the next session was mentoring. The results of the training activities that had been carried out, participants were able to master knowledge and skills that exceeded the expected targets.